Gas discharge in plasma-metal waveguide with varying radius of metal enclosure partially filled by radially non-uniform magnetized plasma - Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2020)
The article presents the results of theoretical study of phase and attenuation characteristics of the symmetric electromagnetic wave in long waveguide structure that partially filled by radially non-uniform plasma immersed in external steady magnetic field. The results of theoretical study of stationary gas discharge sustained by this wave in the considered waveguide structure with slightly varying radius of metal enclosure in the framework of electrodynamic model are presented as well. It was studied the influence of the effective plasma collision frequency on the phase and attenuation wave properties and on the plasma density axial distribution in gas discharge considered for different radial plasma density profiles. Представлено результати теоретичного дослідження фазових характеристик та просторового загасання симетричної електромагнітної хвилі в довгій хвилеводній плазмово-металевій структурі, що частково заповнена радіально-неоднорідною плазмою, яка знаходиться у зовнішньому аксіальному постійному магнітному полі. В межах електродинамічної моделі стаціонарного газового розряду отримано аксіальний розподіл густини плазми, що підтримується власною симетричною хвилею структури. Досліджено також впливи ефективної частоти зіткнень електронів плазми на фазові характеристики та просторове загасання хвилі, а також на аксіальний розподіл густини плазми в газових розрядах, що підтримуються нею, за різних радіальних розподілів густини плазми. Представлены результаты теоретического исследования фазовых свойств и пространственного затухания симметричной электромагнитной волны в длинной волноводной плазменно-металлической структуре, частично заполненной радиально-неоднородной плазмой, помещенной во внешнее аксиальное постоянное магнитное поле. Представлены результаты теоретического исследования аксиального распределения плотности плазмы в стационарном газовом разряде, поддерживаемом симметричной волной, в рассматриваемой волноводной структуре, полученные в рамках электродинамической модели разряда. Исследованы также влияния эффективной частоты столкновений электронов плазмы на фазовые свойства и пространственное затухание волны, а также на аксиальное распределение плотности плазмы в газовых разрядах, поддерживаемых этой волной, для различных радиальных профилей плотности плазмы.